LIFE QUALITY, PSYCHOLOGICAL STATE, TREATMENT AND PREVENTION ADHERENCE EVALUATION IN LOCAL POLYCLINIC PATIENTS - E. V. Indukaeva; S. A. Makarov; O. V. Gruzdeva; T. P. Zhilyaeva; I. L. Strokolskaya (Кардиоваскулярная терапия и профилактика, 2017)
Aim. To evaluate life quality (LQ), specifics of psychological state, level of adherence to treatment and prevention in the covered inhabitants of local outpatient primary institution (polyclinic).Material and methods. Totally, 1082 persons participated, age 21-70 y.o. and older, on dispensary coverage at MBHI “Clinical consulting and diagnostic center” of Kemerovo city. In all participants, the following were studied: prevalence of arterial hypertension, diabetes, hypercholesterolemia, smoking, waist circumference increase, developed coronary heart disease, LQ, adherence and anxiety levels.Results. Under the framework of aged-stratified dispanserization in local polyclinic, 272 males and 810 females investigated. Analysis of age-gender groups by the levels of physical, psychological health, reactive and trait anxiety, treatment adherence did not reveal significant differences. However, for all age groups there is a low level common, of physical and psychological health, and high mean levels of anxiety and treatment adherence. High levels of reactive and trait anxiety found in healthy men and women comparing to the diseased. In all patients in dispanserization, regardless of the presence or absence of disease, there is high treatment adherence.Conclusion. There are high levels found, in chronic psychoemotional stress, anxiety and depression, and adherence level is high in all groups of patients. This might witness on positive attitudes of patients to participation in prevention events and consulting, with the aim for risk factors correction, and decrease of cardiovascular diseases development probability, and in those alredy having such diseases, decrease of severity and complications rate. It is necessary to provide with psychological assistance for improvement of psychoemotional state and personal adaptation potential, level of LQ, for all covered by dispensary observation patients in territory polyclinics.